RANCANG BANGUN ANTENA ARRAY MIKROSTRIP DENGAN FREKUENSI 2,4 GHZ SEBAGAI TRANSCEIVER PENGUATAN SINYAL WIFI ADAPTER - ., Asep Syaiful Rohman (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
Microstip antenna widely applied in the world of telecommunications.  This is because the microstrip antenna has several advantages  when compared to other types of antennas, such as it has a low profile form (thin and small),  has a light weigt, easily  fabricated,  and the price is relatively  cheaper.  But the microstrip antenna also has some disadvantages, those are low gain, low bandwidth, low efficiency, and surface waves. In this final  project   it has been designed  of equilateral  triangle  with  4 elements  microstrip  array  antenna  as reinforcement  of wifi adapter  transceiver.  Microstrip  array antenna  design  formed  by a equilateral  triangle radiator patch with   T-junction  channel. Basic media of this antenna design was using substrates  made form Fiberglass  Efoxy  FR-4  with 1,6 mm substrat  thickness  and dielectric  constant  4,4. The triangle  patch  form based on theoritical  analysis  of cavity  model frequency  2,4 GHz. Parameter  that must be consedered  in the design of the antenna as LAN wireless such as working frequency, input impedance, and SWR (Standing Wave Ratio).  This microstrip  array  antenna  has input  impedance  parameter  values  4,8952+  J 1,2238  Ohm,  SWR1,6432.  This  microstrip  antenna  testing  includes  testing  the  connectivity  using  CMD  available  on PC with windows operating system, testing the download and upload speed using Speedtest.net, and more imfortant than this thesis is the testing of antenna transmit power by using Vistumbler software. As for the result of differences in  the  transmit  power  received  by  the  divice  has  a  minimum  difference  of  0  dBm  and  -5  dBm  maximum difference. Key Word : Antenna Microstrip, Transceiver, Wifi Adapter, Low Profile, Array